Pemanfaatan Teknologi Augmented Reality dengan Marker-Based Tracking sebagai Media Pengenalan Kabupaten Muara Enim - Adeliani Adeliani; Dinda Lestarini; Iin Seprina (Politeknik Harapan Bersama, 2026)
The development of digital technology has increased the demand for more interactive information media, including those used to present regional potential. Muara Enim Regency is rich in culture, industry, and tourism, all of which need to be introduced through more engaging media for both younger generations and the wider community. This study aims to develop an Augmented Reality–based application for introducing Muara Enim Regency using the Marker-Based Tracking method as a response to the need for more immersive and accessible information media. The development process follows the Multimedia Development Life Cycle (MDLC) method, which includes the Concept, Design, Material Collecting, Assembly, Testing, and Distribution phases. The application is implemented using Unity and Vuforia, integrating 3D objects, information panels, and an interactive quiz feature. Functional testing through Black-box Testing shows that all features operate according to specifications without significant issues. User Acceptance Testing (UAT) produced results categorized as very good, indicating that the application is positively received in terms of operational ease, informational clarity, stability, and interaction experience. Therefore, this application is considered suitable as an alternative medium for introducing the potential of Muara Enim Regency and has promising opportunities for further development through additional content and enhanced interactivity.